A 5291‐ppi organic light‐emitting diode display using field‐effect transistors including a c‐axis aligned crystalline oxide semiconductor. Issue 8 (26th June 2019) - Katsui, Shuichi; Kobayashi, Hidetomo; Nakagawa, Takashi; Tamatsukuri, Yuki; Shishido, Hideaki; Uesaka, Shogo; Yamaoka, Ryohei; Nagata, Takaaki; Aoyama, Tomoya; Nei, Kosei; Okazaki, Yutaka; Ikeda, Takayuki; et al.
Abstract: C‐axis‐aligned crystalline‐oxide semiconductor field‐effect transistor (CAAC‐OS FET) can be scaled down to a width and a length of 60 nm. We fabricated an organic light‐emitting diode (OLED) display with more than 5000 ppi, which is required in virtual reality (VR) display applications, using CAAC‐OS FETs as the backplane. Abstract : C‐axis‐aligned crystalline‐oxide semiconductor field‐effect transistor (CAAC‐OS FET) can be scaled down to a width and a length of 60 nm. We fabricated an organic light‐emitting diode (OLED) display with more than 5000 ppi, which is required in virtual reality (VR) display applications, using CAAC‐OS FETs as the backplane.